Exemples atroces et atrocités exemplaires : l’hypotypose dans les canards sanglants en France aux XVIe et XVIIe siècles - Giernatowska, Justyna (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2018)
Canards sanglants fit squarely into the poetics of short, bloody stories, very popular in 16th and 17th century France which is tormented by the Wars of Religion. Those occasional booklets willingly have recourse to hypotyposis, in order to present the brutal scenes of violence in an exceptionally suggestive manner. The rhetorical figure, integrated with the narrative structure of canards, is supposed to have an influence on reader’s imagination, i.a. by means of restrained use of the stylistic devices and impartiality – which often turns out to be illusory – of the crime’s description. However, it can be subject to pathetic amplification and it adapts to the 16th and 17th century prose. By virtue of this approach, that consists in representing the recent events or the most important issues in a distinct, disturbing, but also attractive way, the authors attempt to manipulate emotions, to share their moralizing reflections and inculcate some ethical values into the public, to criticize the social, political or religious phenomena of the time.